How do compact, accessible, and walkable communities promote gender equality in spatial behavior?. (April 2018) - Lo, A. W.-T.; Houston, D.
Abstract: Directing growth towards denser communities with mixed-use, accessible, and walkable neighborhood design has become an important strategy for promoting sustainability, but few studies have examined whether compact development strategies could help reduce within-household gender disparities in spatial behavior by increasing accessibility. We analyze spatial behavior of heterosexual married couples in Southern California based on the 2012 California Household Travel Survey and find that households living in areas with greater regional accessibility and neighborhood walkability have smaller, more centered, and more compact activity spaces overall compared to households in less compact areas, and that married pairs living in more accessible areas have greater equality in the size and centeredness of their activity spaces. We account for residential selection bias in our multivariate analysis and find that a ten unit increase in near-residence Walk Score was associated with a 12–18% decrease in activity space size, a 6–8% decrease in residential distancing, and a 12–13% increase in spatial concentration for both men and women. Men and women, however, had significantly different activity space behaviors regardless of their neighborhood type. Compared to women, men on average had larger activity spaces and conducted their activities farther from home. Overall, results support our hypothesis that compact development provides married couples greater flexibility in how they divide household out-of-home activities by making destinations more convenient and lowering the overall spatial fixity of these activities. Future research and planning efforts should carefully consider which aspects of compact, accessible development are most effective for a given local context.